2018
DOI: 10.4039/tce.2018.22
|View full text |Cite
|
Sign up to set email alerts
|

A unique new species of halophilous water strider of the genus Aquarius Schellenberg (Hemiptera: Gerridae: Gerrinae) endemic to Omura Bay, Nagasaki, Japan

Abstract: A new species of halophilous water strider, Aquarius haliplous Yasunaga, Asanabe, and Nagashima new species (Hemiptera: Gerridae: Gerrinae), is diagnosed and described. This species is endemic to Omura Bay, Nagasaki, southwestern Japan, and has a unique adaptation to this mixohaline habitat. Based on unique morphology and ecology both in the adult and immature forms, this new Aquarius Schellenberg species can be separated unequivocally from a similar species inhabiting freshwater, A. paludum (Fabricius). A key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(31 citation statements)
references
References 12 publications
1
29
1
Order By: Relevance
“…paludum (see Results), Yasunaga et al . (2018) confirmed that A . haliplous could breed at a salinity of 6.0%–28.0‰ in Omura Bay, Nagasaki Prefecture.…”
Section: Methodsmentioning
confidence: 58%
See 4 more Smart Citations
“…paludum (see Results), Yasunaga et al . (2018) confirmed that A . haliplous could breed at a salinity of 6.0%–28.0‰ in Omura Bay, Nagasaki Prefecture.…”
Section: Methodsmentioning
confidence: 58%
“…haliplous (Yasunaga et al . 2018). However, in the nDNA histone H3 region, the sequence was identical to that of A .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations